Two new species of the genus Elasmopus Costa, 1853 (Amphipoda: Gammaridea: Maeridae) from off the Northeast Brazilian Coast - Souza-Filho, Jesser F.; Senna, André R. (Zootaxa, 2009)
The genus Elasmopus has a worldwide distribution with most species living in warm waters. This work describes two new species, both from off the northeast Brazilian coast, including its oceanic banks of Fernando de Noronha Chain. The first new species, E. karamani sp. nov., is easily recognized by palm of gnathopod 2 with a medial concave portion, posterior margin of basis of pereopod 5 and 6 concave, epimeron 3 produced in a sharp spine, and the uropod 3 rami 2.4 times the peduncle length. The other one, E. lejeunei sp. nov., is very similar to E. balkomanus Thomas & Barnard, 1989 and E. lemaitrei Ortiz & Lalana, 1994 in having propodus of gnathopod 2 without palmar corner and posterior margin of basis of pereopod 5 concave. However, it differs from those by presenting gnathopod 2 with a weakly developed process near hinge of dactylus with some robust setae, followed by two tubercles. The propodus inner face presents one ridged line, about 1/3 of propodus length, and perpendicular lines of setae, from the proximal portion of the ridged line almost to the dactylus hinge. A key to all species of the genus Elasmopus recorded in the Brazilian coast is given.